Influence of soil applied cadmium on the growth and cadmium content In Indian spinach (Basella rubra L.) (Chittagong University Journal of Biological Sciences, 2013)
Growth and accumulation of cadmium (Cd) in Indian spinach (Basella rubra L.) grown in three different textured soils treated with various levels of Cd was studied by a pot experiment. In general, Cd application caused a suppression of dry weights of leaves, stems and roots. The increasing application of Cd from 1 to 9 mg Cd kg-1 soil significantly increased Cd concentration in leaf, stem and root from that of the control. The highest concentrations of Cd were found in roots and the lowest concentrations were found in the stems with moderate values in leaves in clay loam soil while in other two soils, the Cd concentrations in leaves and stems were almost similar being lower than those in roots. Positive correlations were found between 0.1 M HCl extractable Cd in soils after harvest and concentrations of Cd in plant parts of Indian spinach. DOI: http://dx.doi.org/10.3329/cujbs.v5i1.13379 The Chittagong Univ. J. B. Sci.,Vol. 5(1 &2):135-147, 2010